2015
DOI: 10.3389/fmicb.2015.01178
|View full text |Cite
|
Sign up to set email alerts
|

Colonial vs. planktonic type of growth: mathematical modeling of microbial dynamics on surfaces and in liquid, semi-liquid and solid foods

Abstract: Predictive models are mathematical expressions that describe the growth, survival, inactivation, or biochemical processes of foodborne bacteria. During processing of contaminated raw materials and food preparation, bacteria are entrapped into the food residues, potentially transferred to the equipment surfaces (abiotic or inert surfaces) or cross-contaminate other foods (biotic surfaces). Growth of bacterial cells can either occur planktonically in liquid or immobilized as colonies. Colonies are on the surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 87 publications
3
39
0
1
Order By: Relevance
“…The findings of the present study entail significant implications for the microbial safety of processed fish-based food products, and food safety in general. In literature, assumptions concerning microbial growth morphology tend to be rather simplistic, as three different situations are normally distinguished based on the specific food microstructure, i.e., (i) planktonic growth in liquid products, (ii) submerged colony growth in gelled products, and (iii) surface colony growth on food surfaces (26,68). In the present study, it was demonstrated that this classification does not always adequately describe real microbial behavior, not even in products with a homogeneous microstructure.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the present study entail significant implications for the microbial safety of processed fish-based food products, and food safety in general. In literature, assumptions concerning microbial growth morphology tend to be rather simplistic, as three different situations are normally distinguished based on the specific food microstructure, i.e., (i) planktonic growth in liquid products, (ii) submerged colony growth in gelled products, and (iii) surface colony growth on food surfaces (26,68). In the present study, it was demonstrated that this classification does not always adequately describe real microbial behavior, not even in products with a homogeneous microstructure.…”
Section: Discussionmentioning
confidence: 99%
“…The term "quantitative microbial ecology" has been suggested [42] for the modeling studies of colonizing microflora. However, an alternative to this term, "predictive microbiology," seems to be applied nowadays as it brought solutions to the above-formulated problems by modeling the microflora's evolution, thus allowing the earlier prediction and information about product procedures and quality by similar means [40,43,44].…”
Section: Development Of Modeling Systems In the Food Industrymentioning
confidence: 99%
“…Since then, different types of modeling techniques have been developed (Table 2) [62,63]. Multi-factorial models [43,50] predict the growth of microbial populations by analyzing the contribution of essential factors involved in the system. Bi-dimensional and tridimensional models combine the different factors incriminated in the food chain [63].…”
Section: Mathematical Models For Predictive Microbiologymentioning
confidence: 99%
“…; Fujikawa and Morozumi ; Pla et al . ; Skandamis and Jeanson ). A commonly used model to characterize the growth of bacteria is the logistic function of Verhulst (Peleg and Corradini ).…”
Section: Introductionmentioning
confidence: 97%
“…Modelling the growth of microbial populations allows for the controllable cultivation of micro-organisms and acts as a tool to effectively monitor and predict the microbial growth in natural and artificial biological communities (Adair et al 1989;Gibson et al 1989). Numerous mathematical models describe microbial growth (Gibson et al 1989;Wijtzes et al 1995;Fujikawa and Morozumi 2005;Pla et al 2015;Skandamis and Jeanson 2015). A commonly used model to characterize the growth of bacteria is the logistic function of Verhulst (Peleg and Corradini 2011).…”
Section: Introductionmentioning
confidence: 99%